Implementasi PSAK 212 Pajak Penghasilan Badan pada PT Erajaya Swasembada Tbk Tahun 2020-2024 - Astari Afridianti; Ingra Sovita (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of PSAK 212(Income Taxes) at PT Erajaya Swasembada Tbk for the 2020–2024 period. The primary focus is to identify temporary and permanent differences, evaluate the fiscal reconciliation process for current and deferred taxes, and examine the compliance of recognition, measurement, presentation, and disclosure based on applicable accounting standards. Using a qualitative descriptive method, the study involves a documentation review of the company’s audited consolidated annual financial statements. The results indicate that PT Erajaya Swasembada Tbk has consistently implemented PSAK 212. The company accurately recognizes deferred tax assets arising from temporary differences, particularly from employee benefit reserves and PKWT accruals. Regarding presentation, the company applies the offsetting principle, reporting deferred tax assets and liabilities net within non-current assets. Furthermore, the Notes to the Financial Statements (CALK) demonstrate high transparency through the disclosure of deferred tax mutations and reconciliation between tax expense and accounting profit. This implementation enhances financial reporting quality, provides accurate fiscal information for stakeholders, and reflects Good Corporate Governance in tax risk management.